Purine metabolites regulate leukemic cell sensitivity toward cytarabine - Xiaowen Zhang; Ang Jia; Jianwei You; Zixuan Zhuang; Yinfei Wang; Ting Liu; Xingrong Du; Linzhang Huang; Peng Li; Tong-Jin Zhao; Craig T. Jordan; Li Chen; et al. (Haematologica)
Not available.